UTILIZATION OF LOCAL FOOD INGREDIENTS AND SPICES TO MEET NUTRITIONAL REQUIREMENTS, STRENGTHEN IMMUNITY, AND ADDRESS MINOR AILMENTS IN HOUSEHOLDS - Afifah Kusuma Vardhani; Puteri Fannya; Nadiya Nurul Afifah; Rizqia Rahmah; Yolan Adis Safitri; Aulia Salsabila; Mochamad Fauzan W.; Raihan Fakhri P. S. (LPPM Univ. Ibn Khaldun Bogor, 2026)
The Baitul Maal Foundation of PLN (YBM PLN) Research Institute, located at Jl. PLN Duren Tiga no. 102, Pancoran, South Jakarta, has dozens of fostered families who are underprivileged families in the surrounding area. Scholarships for schoolchildren have been in place as a sort of guidance. Students fostered by YBM PLN require nutritional support to help them learn in school and strengthen their immune systems. As a result, community service and education activities that reinforce the concept of eating healthy and nutritious foods as part of a clean and healthy living behaviour (PHBS) are essential. As a result, there is a greater understanding and awareness of the need of proper nutrition for child development, particularly throughout the school years. Fulfilling family nutrition needs, beginning with nutritious and balanced home meals in combination with Indonesian herbs, will boost immunity, prevent disease, and promote students' learning activities.